The roles of microRNAs in tumorigenesis and angiogenesis - Yang, Weining (e-Century Publishing Corporation, 2010)
MicroRNAs (miRNAs) are short, non-coding sequences that control gene expression via translational regulation. Through interactions with the 3'-untranslated region of messenger RNA, miRNAs trigger translational repression and play a key role in developmental timing. Furthermore, many miRNA groups have now been shown to regulate various processes in tumorigenesis, including angiogenesis and metastasis. These links highlight the importance of microRNA research in further understanding cancer development. This review article summarizes the current state of microRNA research, with a focus on the roles of microRNAs in various cancer types. Up to date knowledge of the structure and biogenesis pathway of microRNA are also reviewed.